Gender Differences, Framing, and Responsibility in Investment Decision-Making: An Experimental Study - Barkah Susanto; Naufal Afif; Betari Maharani; Nur Laila Yuliani; Muhammad Ridhwan Ab Aziz (Journal of Accounting and Investment, 2023)
Research aims: This study aims to investigate the effect of gender, framing, and responsibility on investment decision-making. Design/Methodology/Approach: This experimental study used a subject design of 2 x 2 x 2, in which 81 doctoral students participated. Furthermore, cross-tabulation was employed to analyze and examine the hypotheses.Research findings: The results revealed that positive and negative framing and responsibility levels would affect investment decision-making. This research also uncovered differences in risk preferences in decision-making between men and women. Additionally, both genders had varying preferences in making similar decisions.Theoretical contribution/Originality: Several studies have shown that when information is presented differently, here in after referred to as framing, it significantly influences decisions. However, the decision-making determination is influenced not only by framing but also by other variables. In this study, the framing variable, therefore, was tested jointly with the variables of responsibility and gender differences.